Implementasi Sistem Informasi Perpustakaan pada Sekolah Indonesia Davao Filipina Menggunakan CMS SLiMS - Sisephaputra, Bonda; I Kadek Dwi Nuryana; Aries Dwi Indriyanti; Ghea Sekar Palupi (Abimanyu : Jornal of Community Engagement, 2025)
This community service aims to develop a Library Information System at Indonesian School of Davao, Philippines, to improve the efficiency of library management and the accessibility of learning resources for students and teachers. The system was built using the Content Management System (CMS) SLiMS, an open-source platform designed for managing library operations digitally, including inventory recording, book lending, and returns. In implementing this Community Service Program (PKM), the methods used to address the problems at Indonesian School of Davao (SID) were the Diffusion of Science and Technology (Ipteks) and Training. This activity also involved continuous evaluation to ensure the success of the program. The results showed increased efficiency in library management, easier access to information, and improved skills of library staff in using CMS SLiMS. In conclusion, the application of information technology through CMS SLiMS in the library of Indonesian School of Davao has contributed positively to enhancing the teaching and learning process.